Mapping the attributions of parents: a client-centered dynamic approach to assessing vulnerable caregivers and their young children. (2nd January 2018) - Bohr, Yvonne; Dhayanandhan, Bramilee; Kanter, Deborah; Holigrocki, Rick; Armour, Leigh; Baumgartner, Emma
ABSTRACT: In recent years much attention has been directed to the development of effective caregiving interventions in response to a growing body of research that links parenting quality to healthy developmental outcomes of children. Many existing empirically validated interventions designed for caregivers are highly didactic and take a primarily behavioral, psycho-educational, and skill-building approach. Although there is much evidence that these interventions are useful for a subgroup of caregivers, they may not be adequate in addressing the needs of more vulnerable caregivers who themselves may have histories of trauma. For those caregivers, a highly customized and supportive framework for delivering parenting education may be indicated if an intervention is to be successful and generalizable. This article provides an overview of a dynamic assessment Mapping the Attributions of Parents (MAP) designed for clients who may benefit from an individualized approach to learning how to be sensitive and responsive caregivers to their young children. The person-centered, interactive approach that characterizes the MAP assessment provides the client and therapist with data to be used for treatment planning, while offering immediate therapeutic benefits. An illustrative case study is provided.